1992
DOI: 10.1128/mcb.12.6.2662
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of the CD19 gene is a target for the B-cell-specific transcription factor BSAP.

Abstract: The CD19 protein is expressed on the surface of all B-lymphoid cells with the exception of terminally differentiated plasma cells and has been implicated as a signal-transducing receptor in the control of proliferation and differentiation. Here we demonstrate complete correlation between the expression pattern of the CD19 gene and the B-cell-specific transcription factor BSAP in a large panel of B-lymphoid cell lines. The human CD19 gene has been cloned, and several BSAP-binding sites have been mapped by in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(208 citation statements)
references
References 38 publications
10
196
1
1
Order By: Relevance
“…The specific binding of PAX5 to the human CD19 promoter was shown in a previous study (Kozmik et al, 1992). In a subsequent study we showed that PAX5 binds to both, the promoter and enhancer, of the mouse Cd19 gene loci (Walter et al, 2008).…”
Section: Pax5 Binds To the Cd19 Promoter And Enhancer In B Cellssupporting
confidence: 68%
“…The specific binding of PAX5 to the human CD19 promoter was shown in a previous study (Kozmik et al, 1992). In a subsequent study we showed that PAX5 binds to both, the promoter and enhancer, of the mouse Cd19 gene loci (Walter et al, 2008).…”
Section: Pax5 Binds To the Cd19 Promoter And Enhancer In B Cellssupporting
confidence: 68%
“…Four SNPs were detected in the promoter region, but these sites are not considered to be binding sites for the important transcription factors such as B cell lineage-specific antigen promoter (BSAP, Pax5). 52 In conclusion, this study demonstrated a number of polymorphisms within human CD19. Association of CD19 3'UTR dinucleotide repeat polymorphism, or another gene in linkage disequilibrium with it, with susceptibility to SLE was suggested.…”
Section: Genes and Immunity Antinuclear Antibodies (Sato S Personal mentioning
confidence: 57%
“…The Tg vector, pCD19-FLIP, encoding Flag-muFLIP under the control of the B cell-specific CD19 promoter was constructed in the pBSKS II(-) vector and contained (a) in the NotI site, a 6.4-kb EagI fragment of vector CD19 XS (containing nucleotides -6435 to -15 of hCD19) [46]; (b) in the BamHI/XhoI sites, nucleotides 421-1592 of rabbit g -globin (comprising the end of exon 2, intron 2, exon 3 and the poly A addition signal) [4]; (c) in the blunted EcoRI site of the g -globin sequence, a 1525-nucleotide sequence encoding Flag-mouse FLIP L (MDYKDDDDKEFGL followed by amino acid residues 2-481 of mouse FLIP L ) [20]. Tg mice were generated by microinjection of the BssHII fragment of pCD19-FLIP into fertilized (C57BL/6×DBA/2) F2 oocytes, and screened by PCR using oligonucleotides JT1822 5'-TCA-AGAGTGAGGCGGTTTGACC-3' and JT1823 5'-TCCTGAT-TCCTGGATGGATGTC-3'.…”
Section: Transgenic Micementioning
confidence: 99%